2020
DOI: 10.7554/elife.58108
|View full text |Cite
|
Sign up to set email alerts
|

Sperm-specific COX6B2 enhances oxidative phosphorylation, proliferation, and survival in human lung adenocarcinoma

Abstract: Cancer testis antigens (CTAs) are proteins whose expression is normally restricted to the testis but anomalously activated in human cancer. In sperm, a number of CTAs support energy generation, however whether they contribute to tumor metabolism is not understood. We describe human COX6B2, a component of cytochrome c oxidase (complex IV). COX6B2 is expressed in human lung adenocarcinoma (LUAD) and expression correlates with reduced survival time. COX6B2, but not its somatic isoform COX6B1, enhances activity of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 54 publications
(78 reference statements)
2
28
0
Order By: Relevance
“…Similar to our results, a previous study reported that FTO expression was positively related to dextrose oxidation rates and levels of genes related to oxidative phosphorylation in skeletal muscle [47]. It has been shown that oxidative phosphorylation plays significant roles in lung cancer proliferation, invasion, metastasis, and drug resistance [48][49][50]. erefore, it is likely that genetic alterations of FTO regulate the progression of NSCLC by affecting cellular oxidative phosphorylation levels.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our results, a previous study reported that FTO expression was positively related to dextrose oxidation rates and levels of genes related to oxidative phosphorylation in skeletal muscle [47]. It has been shown that oxidative phosphorylation plays significant roles in lung cancer proliferation, invasion, metastasis, and drug resistance [48][49][50]. erefore, it is likely that genetic alterations of FTO regulate the progression of NSCLC by affecting cellular oxidative phosphorylation levels.…”
Section: Discussionsupporting
confidence: 90%
“…As a consequence, subsequently acquired (pseudo)meiotic functions may help the cancer cells to disturb normal cell cycle regulation and DNA repair mechanisms in order to evade checkpoints and apoptosis [ 10 ]. Indeed, and consistently with previous reports on CT genes [ 38 ], the expression of the meiosis specific gene HORMAD1 [ 39 , 40 ], the MAGE-A gene family [ 41 ], and the sperm specific cytochrome c oxidase COX6B2 [ 42 , 43 ], we found that a high GC signature score correlates with poor prognosis in lung adenocarcinoma.…”
Section: Discussionsupporting
confidence: 91%
“…[ 49 ] COX6B2 and NDUFB9 are the components in the mitochondrial electron transport chain. [ 50,51 ] GSN is located to the mitochondrial outer membrane and protects cell from death. [ 52,53 ] Mitochondria not only are the powerhouse of cells but also play essential roles in iron homeostasis, lipid metabolism and cell death signaling.…”
Section: Resultsmentioning
confidence: 99%